Achieving expertise in sport: Deliberate practice, adaptation, and periodization of training - Lidor, R.; Tenenbaum, G.; Ziv, G.; Issurin, V. (Kinesiology Review, 2016)
Deliberate practice (DP), an activity aimed at enhancing an individual`s performance, has been reported to be crucial for achieving a state of expertise in various domains, such as education, music, and sport. In this article, the relationships between DP and the process of athletic performance adaptation are explored by elaborating on the main principle of the theory of training—periodization. We argue that periodization should be considered as a mechanism for ensuring DP, and that the implementation of periodization principles (cycles and phases) in DP activities can facilitate adaptation processes leading to expert performance. We describe the characteristics and features of DP, review a series of studies on DP and athletic performance (N = 21), discuss the importance of periodization in sport training, and outline a number of benefits of periodization. A model that emphasizes the link between periodization and DP activities in each phase of sport development is proposed, and a number of research approaches to address periodization are discussed.